1987
DOI: 10.1159/000111625
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of <i>L</i>-Monosodium Glutamate Promote Neuronal Growth and Differentiation in vitro

Abstract: Monosodium glutamate given at a concentration of 5 x 10–6M to whole-brain dissociated cultures of 18-day-old rats promotes neuronal growth. Neurons are larger due to an increased size of both cytoplasm and nucleus. Rough endoplasmic reticulum is more developed and mitochondria are more abundant. Synaptic vesicles are significantly increased in number with respect to control cultures. Synapses are more abundant and show a more differentiated morphology. These findings are interpreted as evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…ation and synaptogenesis in the developing nervous system. For example, in vitro studies show a trophic effect of low concentrations of GLU on neurite outgrowth and synapse formation (37,38). In vivo NMDA treatment also increases synapse formation in occipital cortex of postnatal rats (39) (for reviews see 40,41).…”
Section: Discussionmentioning
confidence: 99%
“…ation and synaptogenesis in the developing nervous system. For example, in vitro studies show a trophic effect of low concentrations of GLU on neurite outgrowth and synapse formation (37,38). In vivo NMDA treatment also increases synapse formation in occipital cortex of postnatal rats (39) (for reviews see 40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Aruffo et al have found that glutamate application on postnatal rat whole-brain dissociated cell cultures promotes neuronal growth and differentiation as compared to control cultures (Aruffo et al 1987). Many studies have reported that the glutamate NMDAR activation promotes neurite outgrowth from cerebellar granule cells (Pearce et al 1987) and dendritic outgrowth and branching of hippocampal cells (Brewer and Cotman 1989;Mattson et al 1988b;Wilson et al 2000).…”
Section: Neuroblastsmentioning
confidence: 99%
“…Glutamate is known to promote neuronal growth, to produce associated maturational cytological changes (Aruffo et al, 1987), and effect dendritic growth cone navigation (Mattson et al, 1988). During development, glutamate and its receptors have many important roles (Gu et al, 1996;Metzger et al, 1998;Atwood and Wojtowicz, 1999).…”
Section: Introductionmentioning
confidence: 99%